Synthesis and Anticancer Evaluation of Thiazacridine Derivatives Reveals New Selective Molecules to Hematopoietic Neoplastic Cells - de Melo Rego, Moacyr J.B.; de Sena, Wanessa l.b.; de Moura, Ricardo O.; Jacob, Iris T.T.; Lins e Lins, Thiago U.; Pereira, Michelly C.; do Carmo A. Lima, Maria; Galdino-Pitta, Marina R.; da R. Pitta, Ivan; da Rocha Pitta, Maira G. (Combinatorial Chemistry & High Throughput Screening, 2017)
Aim and Objective: Cancer has become one of the leading causes of morbidity and mortality worldwide. Limitations associated with existing agents increase the need to develop more effective anticancer drugs to improve the therapeutic arsenal available. The aim of this study was to synthesize and evaluate the antiproliferative effects of three new thiazacridine derivatives. Material and Methods: Using a three steps synthesis reaction, three novel thiazacridine derivatives were obtained and characterized: (Z)-5-acridin-9-ylmethylene-3-(4-methyl-benzyl)-4-thioxo-thiazolidin- 2-one (LPSF/AC-99), (Z)-5-acridin-9-ylmethylene-3-(4-chloro-benzyl)-4-thioxo-thiazolidin-2- one (LPSF/AC-119) and (Z)-5-acridin-9-ylmethylene-3-(3-chloro-benzyl)-4-thioxo-thiazolidin-2- one (LPSF/AC-129). Toxicity and selectivity assays were performed by colorimetric assay. Then, changes in cell cycle and cell death induction mechanisms were assessed by flow cytometry. Results: All compounds exhibited cytotoxicity to Raji (Burkitt's lymphoma) and Jurkat (acute T cell leukemia) cells, where LPSF/AC-119 showed best IC50 values (0.6 and 1.53 μ M, respectively). LPSF/AC-129 was the only cytotoxic compound in glioblastoma cell line NG97 (IC50 = 55.77 μ M). None of the compounds were toxic to normal human cells and induced neoplastic cell death primarily by apoptosis. Conclusion: All derivatives were more cytotoxic to hematopoietic neoplastic cells when compared to solid tumor derived cells. All three compounds are promising for in vivo and combination therapy studies against cancer.
Keywords: Cancer